2021
DOI: 10.1371/journal.pone.0239214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical activity on reducing the risk of diabetic retinopathy progression: 10-year prospective findings from the 45 and Up Study

Abstract: Objective To examine the association of physical activities (PA) with diabetic retinopathy (DR) progression based on a 10-year follow-up of a large cohort of working-aged diabetic populations in Australia. Methods Nine thousand and eighteen working-aged diabetic patients were enrolled from the baseline of the 45 and Up Study from New South Wales, Australia. Self-reported PA collected by questionnaire at baseline in 2006 was graded into low (<5 sessions/week), medium (≥5–14), and high (≥14) levels. Retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
4
14
0
Order By: Relevance
“…Another study indicated that frequent leisure-time physical activity reduced the severity of DR after adjusting for gender, duration, age at onset of diabetes, kidney function, triglycerides, systolic blood pressure, and BMI [ 112 ]. Yan et al have shown that physical activity was related to decreased risk of retinal photocoagulation as well as DR progression in the Australian population of working-aged diabetic patients [ 113 ]. Association between physical activity and DR is influenced by various modifiers, including BMI, gender, history of CVD, diabetes (in family), and insulin therapy [ 113 ].…”
Section: Targeted Mitigationmentioning
confidence: 99%
“…Another study indicated that frequent leisure-time physical activity reduced the severity of DR after adjusting for gender, duration, age at onset of diabetes, kidney function, triglycerides, systolic blood pressure, and BMI [ 112 ]. Yan et al have shown that physical activity was related to decreased risk of retinal photocoagulation as well as DR progression in the Australian population of working-aged diabetic patients [ 113 ]. Association between physical activity and DR is influenced by various modifiers, including BMI, gender, history of CVD, diabetes (in family), and insulin therapy [ 113 ].…”
Section: Targeted Mitigationmentioning
confidence: 99%
“…Detailed study methods have been described in earlier studies. 14 , 15 The conduct of the 45 and Up Study was approved by the University of New South Wales Human Research Ethics Committee. The study protocol was approved by the Royal Victorian Eye and Ear Hospital Human Research Ethics Committee (17/1330HS/20).…”
Section: Methodsmentioning
confidence: 99%
“…Increasing physical activity reduces the risk of developing diabetic retinopathy [ 80 , 81 ]. Kuwata et al showed that higher levels of physical activity were independently associated with a lower incidence of DR in patients with type 2 diabetes [ 82 ].…”
Section: Physical Activitymentioning
confidence: 99%